The Role of Intelligence in Mitigating the Risk of Social Conflict Disasters in the 2019 Elections - Widyasandra*, Adelia Rizki; Puspito Sari, Deffi Ayu; Bangun, Ernalem; Widodo, Pujo; Saragih, Herlina Juni Risma; Kusuma, Kusuma; Wilopo, Wilopo (Riwayat: Educational Journal of History and Humanities, 2024)
This study explores the critical role of intelligence in mitigating the potential risks of social conflict disasters during the 2019 elections in Indonesia. In the context of democratic processes, elections serve as a pivotal juncture where societal tensions can escalate, leading to potential conflicts and upheavals. This research investigates how intelligence, encompassing strategic information gathering, analysis, and dissemination, can contribute to the prevention and management of such risks. By delving into the proactive measures taken by intelligence agencies this study aims to unveil the ways in which timely and accurate information can shape policies and interventions aimed at averting social conflict disasters. Findings from this research contribute to the broader discourse on the nexus between intelligence, political stability, and conflict prevention. The insights gleaned may inform future electoral strategies and enhance the effective ess of intelligence-led initiatives in safeguarding democratic processes from the destabilizing forces of social conflict. Ultimately, this study underscores the imperative for a holistic and collaborative approach in harnessing the power of intelligence to foster resilient and peaceful democratic societies.